Isolation, identification, and evaluation of antimicrobial activity of fungi isolated from marine samples collected at Bach Long Vi Island - Nguyen, Mai Anh; Vu, Thu Huyen; Nguyen, Hoang Duong; Doan, Thi Mai Huong; Pham, Van Cuong; Le, Thi Hong Minh (Vietnam Journal of Marine Science and Technology, 2026)
This study aimed to isolate and evaluate the antimicrobial properties of fungi collected from Bach Long Vi Island. Seventeen fungal isolates were obtained from fifteen marine samples collected from various locations around the island. The antimicrobial activity of ethyl acetate extracts from these isolates was assessed using the broth microdilution method against seven test microorganisms. The findings indicated that a significant proportion of the isolates demonstrated potent antimicrobial activity, with 82% inhibiting the growth of at least three pathogenic microbes. All fungal isolates exhibited highly variable inhibitory effects against Enterococcus faecalis, with minimum inhibitory concentrations (MIC) ranging from 32 µg to 256 µg. Additionally, eleven of the seventeen fungal strains showed activity against Candida albicans. Notably, strains CL475, CL503, and CL508 exhibited antimicrobial activity against 4-5 target microbial species and were further analyzed for taxonomic identification. The results revealed that strain CL503 and CL508 belong to Aspergillus versicolor, CL508 belongs to Aspergillus nidulans, and strain CL475 was identified as Penicillium malachiteum. Phylogenetic analysis of these promising isolates was conducted using MegaX software. The results of this study suggest that the production and extraction of bioactive compounds by marine fungi may serve as a.